2011
DOI: 10.1007/s00595-011-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinoscopy-assisted esophagectomy for esophageal cancer in patients with serious comorbidities

Abstract: MAE is feasible for esophageal cancer patients with serious comorbidities and may decrease morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…In 2015, the Japanese scholar Hitoshi Fujiwara systematically reported a method of cervical mediastinoscopy combined with laparoscopic esophagectomy; since then, this procedure has been gradually applied worldwide (4,5). Some retrospective studies have shown that compared to TLE, MATHE further reduces surgical trauma, and it seems to be more advantageous in protecting respiratory function (6)(7)(8). However, there are currently no multicenter randomized controlled studies comparing MATHE with TLE for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the Japanese scholar Hitoshi Fujiwara systematically reported a method of cervical mediastinoscopy combined with laparoscopic esophagectomy; since then, this procedure has been gradually applied worldwide (4,5). Some retrospective studies have shown that compared to TLE, MATHE further reduces surgical trauma, and it seems to be more advantageous in protecting respiratory function (6)(7)(8). However, there are currently no multicenter randomized controlled studies comparing MATHE with TLE for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the indications and contraindications for the MAE are still controversial, and there is no comprehensive and recognized standard. Many comparative studies have demonstrated the feasibility of MAE, and in the course of long-term follow-up, the treatment effect is similar to transthoracic esophagectomy [ 2 , 16 , 17 ]. MAE avoids transthoracic operations, and it can be considered as a more friendly technique for patients with poor cardiac and pulmonary function, or a history of pleural disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For esophageal cancer, mediastinoscopy was introduced into THE to improve visibility and handling in transcervical procedures; it enables safe esophageal dissection with lymph node sampling without any blind dissection. Since the first report by Bumm et al in 1993, which referred to the method as “endodissection of the thoracic esophagus,” there have been a limited number of reports of THE with mediastinoscopic assistance, initially from Europe and, since 2004, from Japan and China . In 2004, Tangoku et al reported on the short‐term outcomes of mediastinoscopy‐assisted THE, often abbreviated as MATHE, using a compact mediastinoscope designed for Japanese patients …”
Section: Mediastinoscopy‐assisted Thementioning
confidence: 99%
“…Since the first report by Bumm et al in 1993, (23) which referred to the method as "endodissection of the thoracic esophagus," there have been a limited number of reports of THE with mediastinoscopic assistance, initially from Europe and, since 2004, from Japan and China. (9,10,(23)(24)(25)(26)(27)(28)(29)(30) In 2004, Tangoku et al reported on the short-term outcomes of mediastinoscopy-assisted THE, often abbreviated as MATHE, using a compact mediastinoscope designed for Japanese patients. (9) Mediastinoscopy-assisted THE has been generally indicated as radical surgery for distal and junction tumors in Western countries (23)(24)(25) and as a less radical or limited surgery for clinical T1-2 or stage I-II tumors in any location in ESCC patients at high-risk for thoracotomy in Asia.…”
Section: Mediastinoscopy-assisted Thementioning
confidence: 99%
See 1 more Smart Citation